Dental Pulp Stem Cells: A New Cellular Resource for Corneal Stromal Regeneration - Syed-Picard, Fatima N. (Stem Cells Transl Med, 2015)
Corneal blindness afflicts millions of individuals worldwide and is currently treated by grafting with cadaveric tissues; however, there are worldwide donor tissue shortages, and many allogeneic grafts are eventually rejected. Autologous stem cells present a prospect for personalized regenerative medicine and an alternative to cadaveric tissue grafts. Dental pulp contains a population of adult stem cells and, similar to corneal stroma, develops embryonically from the cranial neural crest. We report that adult dental pulp cells (DPCs) isolated from third molars have the capability to differentiate into keratocytes, cells of the corneal stoma. After inducing differentiation in vitro, DPCs expressed molecules characteristic of keratocytes, keratocan, and keratan sulfate proteoglycans at both the gene and the protein levels. DPCs cultured on aligned nanofiber substrates generated tissue-engineered, corneal stromal-like constructs, recapitulating the tightly packed, aligned, parallel fibrillar collagen of native stromal tissue. After injection in vivo into mouse corneal stroma, human DPCs produced corneal stromal extracellular matrix containing human type I collagen and keratocan and did not affect corneal transparency or induce immunological rejection. These findings demonstrate a potential for the clinical application of DPCs in cellular or tissue engineering therapies for corneal stromal blindness.